About Complexity of FFT Algorithms for Length of q × 2p - Barseghyan, Rafayel V . (Mathematical Problems of Computer Science, 2021)
The paper presents logarithmic formula which allows to compute the exact number of necessary operations for computing the discrete Fourier transform (DFT) of an arbitrary q × 2 p - length, where q is an odd integer.